POTENTIAL FOR IMPLEMENTING GREEN ECONOMY AND BLUE ECONOMY IN SUSTAINABLE GLOBAL ECONOMY DEVELOPMENT AT THE G20 FORUM WITH CIRCULAR ECONOMY AS NATIONAL ENVIRONMENTAL POLICY - Frederick Rudy Sentosa Rajagukguk; Hastuti Handayani Harahap; Indra Welly Arifin (RADJA PUBLIKA, 2024)
This research aims to describe the potential for implementing the Green Economy and Blue Economy towards Sustainable Global Economic Development at the G20 Forum with Circular Economy as National Environmental Policy. This research is quantitative research using a survey method. The data collection method in this research, the researcher tries to find information related to this discussion in the form of facts, opinions and archival records. The data analysis technique in this research uses Partial Least Square (PLS). The research results of the first hypothesis were accepted that the Green Economy (X1) had an effect on the Circular Economy (Z). The second hypothesis is rejected that the Blue Economy (X2) has no effect on the Circular Economy (Z). The third hypothesis is accepted that the Green Economy (X1) influences the Global Economy (Y). The fourth hypothesis is accepted that the Blue Economy (X2) influences the Global Economy (Y).The fifth hypothesis is accepted that Circular Economy (Z) influences the Global Economy (Y).The sixth hypothesis is accepted that Green Economy (X1) has a significant effect on Global Economy (Y) through Circular Economy (Z). The seventh hypothesis is accepted. Blue Economy (X2) has a significant effect on Global Economy (Y) through Circular Economy (Z).